Age of Information Joint Optimization for an Energy Harvesting Network With Erasure Channel - Qihang Qin; Hengzhou Ye (IEEE Access, 2024)
AoI (Age of Information), a measure of data freshness, is an important consideration in the optimal design of energy harvesting IoT(Internet of Things). Existing AoI studies tend to optimize only for the base station scheduling process or only for the source node update process, and rarely consider the energy constraints and unreliable channels. Therefore, a joint optimization strategy is proposed for an energy harvesting IoT scenario based on heterogeneous source nodes with erasure channels. Based on the energy constraint and channel quality, the base station selects the preferred source node for sample transmission based on the difference in AoI benefit and time cost brought by selecting different source nodes. The source node determines the sample collection moment by taking into account the impact of energy harvesting on the sample collection and transmission, as well as the impact of sample collection on the AoI. Simulation analysis shows that the method can obtain better long-term average AoI in different scenarios than baseline methods.